Why Sociology Needs Science Fiction. (August 2018) - Hirschman, Daniel; Schwadel, Philip; Searle, Rick; Deadman, Erica; Naqvi, Ijlal
Using sci-fi's metaphors, ideal types, and counterfactuals to consider our real-world problems, old and new.